Uma nova concepção de inversor multinível para aplicação em UPS - Oliveira, Lincoln Moura de (2009)
This work deals with the theoretical analysis, design methodology and laboratory implementation of a 3kVA on-line mode Uninterruptible Power Supply (UPS) composed by a multilevel inverter based on a transformer with multiple secondaries and an active power factor correction input stage composed by a diode rectifier in series with a boost converter.The main motivation for this study is to assess the benefits of multilevel inverters in low power (<10kVA) applications. A 3kVA Uninterruptible Power Supply (UPS) with output and input voltage of 220V and 60Hz, has been implemented. Simulation and experimental results for a single phase prototype are conducted to validate the proposed idea. The utilization of low frequency operation inverters promotes low EMI, lower switches stresses, very low commutation losses and consequently higher efficiency. The multilevel converter here used isolates the load from the grid due to the multi-windings transformer intrinsic to the topology. The on-line mode of the UPS (no battery mode) has been implemented. Simulation and experimental results for a single-phase prototype are presented to validate the proposed converter. The UPS presented an efficiency of 90%